Design and fabrication of motorized car jack / Muhammad Irfan Naqiuddin Talib and Mohd Fadzli Ismail - Talib, Muhammad Irfan Naqiuddin; Ismail, Mohd Fadzli (School of Mechanical Engineering, 2023)
This project aimed to address the problem of car users neglecting car care due to their busy lives. Many assumed that as long as their car could still move, it did not need to be inspected. However, this negligence caused car tires to wear, increasing the risk of accidents due to flat or broken tires. When such incidents occurred, car users often struggled to change their tires using the car jack tool, especially women and elderly people due to the required strength. Therefore, a motorized jack was designed and fabricated to be low cost, easy to operate, require less human energy and additional work, and most importantly, safe, reliable, and able to raise and lower the level using a remote. The product focused on common cars on the roads and could jack up cars up to 1.5 Ton. The motorized jack was designed using SolidWorks and fabricated using a combination of steel pipes, hydraulic cylinder, DC motor, and power adaptor. The user could simply place the jack under the car's designated lifting point and operate it using a remote control. The results showed that the motorized jack efficiently raised and lowered cars without requiring additional effort, saving time and ensuring safety. Overall, this motorized jack is a practical solution for car users who struggle with changing their tires using a car jack tool, providing a safe and efficient alternative.